2019
DOI: 10.1016/j.ast.2019.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Control of cylinder wake flow and noise through a downstream porous treatment

Abstract: Various passive and active methods have been developed to control flow separation from bluff bodies. However, these methods require adjusting features of the solid surface, such as modifying its geometry or porosity, or applying external force or momentum. This paper develops an off-body-based method, without adjusting any features of the solid surface, for controlling the unsteady flow separation by fixing porous materials downstream of bluff bodies. Numerical study on flow past a circular cylinder at a subcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…As can be seen, there are good agreement for second-order statistics with both simulation result from Ma et al [28] and Lehmkuhl et al [29] and experimental results from Parnaudeau et al [30]. More studies on the numerical validation can be also found in [12].…”
Section: Numerical Validationsupporting
confidence: 73%
See 1 more Smart Citation
“…As can be seen, there are good agreement for second-order statistics with both simulation result from Ma et al [28] and Lehmkuhl et al [29] and experimental results from Parnaudeau et al [30]. More studies on the numerical validation can be also found in [12].…”
Section: Numerical Validationsupporting
confidence: 73%
“…The studies mentioned above control the flow by coating porous materials on the cylinder surface, while Xu et al [12] recently developed an off-body-based flow control method, where the porous material was fixed downstream rather than coated on the cylinder surface. The numerical results show that the porous material located downstream the cylinder is another effective method for suppressing pressure fluctuations of the cylinder surface.…”
Section: Introductionmentioning
confidence: 99%
“…The novel framework can reduce the noise efficiently without compromising the aerodynamic performance. Xu et al [21] developed an off-body-based method to control the unsteady flow separation by fixing porous materials downstream of bluff bodies. They studied the flow past a circular cylinder at a subcritical Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…5 Therefore, the numerical computation of aerodynamic and aeroacoustic characteristics of bluff bodies (mainly circular cylinders) have received extensive attention. [6][7][8][9][10][11][12][13][14][15] In this paper, we shall concentrate on a passive flow control method [16][17][18][19][20][21][22][23] using wavy circular cylinders for reducing the aerodynamic drag and aeroacoustic sound.…”
Section: Introductionmentioning
confidence: 99%